2009
DOI: 10.2174/157016109789043946
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Sodium-Phosphate Cotransporter Pit-1 and its Role in Vascular Calcification

Abstract: Vascular calcification is caused by the deposition of basic calcium phosphate crystals in blood vessels, myocardium, and/or cardiac valves. Calcification decreases artery wall compliance, and arterial calcification is associated to mortality in hyperphosphatemic renal failure and diabetes mellitus. The calcification of the tunica media characterizes the arteriosclerosis observed with age, diabetes and end stage-renal disease, and it can develop independently from intima calcification. As part of the vascular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 104 publications
1
9
0
1
Order By: Relevance
“…A recent experimental study showed that SPL inhibits transdifferentiation of VSMCs into osteoblast-like cells by downregulating Pit-1 and prevents VC in klotho-hypomorphic mice (39). In addition, Pit-1 silencing suppressed all the VC-related genes in the cultured VSMCs (16,39). In our study, CKD rats showed upregulation of Pit-1 and Runx2, whereas SPL attenuated these increases independently of plasma aldosterone and ANG II concentration.…”
Section: F973supporting
confidence: 52%
See 2 more Smart Citations
“…A recent experimental study showed that SPL inhibits transdifferentiation of VSMCs into osteoblast-like cells by downregulating Pit-1 and prevents VC in klotho-hypomorphic mice (39). In addition, Pit-1 silencing suppressed all the VC-related genes in the cultured VSMCs (16,39). In our study, CKD rats showed upregulation of Pit-1 and Runx2, whereas SPL attenuated these increases independently of plasma aldosterone and ANG II concentration.…”
Section: F973supporting
confidence: 52%
“…Pit-1, expressed in various cells, is a sodium-P i cotransporter that regulates P i entry into cells (16). P i entry into VSMCs through Pit-1 is the first critical step in the VC cascade (14).…”
Section: F973mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the minimal and late onset of the symptoms because no neuronal damage occurs during the early stages of IBGC. Studies on the pathogenesis of vascular calcification induced by phosphate showed that SLC20A1 has a determinant role in the mineralization of vascular cells in vitro [19], [20]. For this reason, we propose that both SLC20A1 and SLC20A2 might be involved in the pathogenesis of FIBGC.…”
Section: Discussionmentioning
confidence: 83%
“…As principais biomoléculas responsáveis pelo processo de biomineralização descritas atualmente são: (i) fosfatase alcalina, também denominada TNAP (fosfatase alcalina não específica de tecido), que apresenta atividade fosfomonohidrolítica, produzindo fosfato a partir, principalmente, de pirofosfato (PP i ) e ATP; (ii) nucleosídeo trifosfato difosfohidrolase 1 (NPP1), enzima responsável pela formação de PP i a partir de nucleosídeos fosforilados; (iii) uma fosfomonohidrolase encontrada especificamente dentro das vesículas, denominada PHOSPHO1, responsável pelo aumento da concentração de P i intravesicular acoplado à degradação de fosfolipídios, através da hidrólise de fosfocolina e fosfoetanolamina (Roberts et al, 2004); (iv) transportadores de P i PiT-1 e PiT-2 (Caverzasio et al, 1988;Montessuit et al, 1991;Palmer et al, 1997), proteínas também chamadas de cotransportadores Na + /Pi do tipo III, e originalmente identificadas como receptores retrovirais (Collins et al, 2004), atualmente estão emergindo como importantes moléculas envolvidas tanto no metabolismo de Pi ósseo quanto em processos patológicos, como calcificação induzida por hiperfosfatemia do tecido vascular e osteoartrite (Zoidis et al, 2004;Cecil et al, 2005;Li et al, 2006;Li e Giachelli, 2007;Yoshiko et al, 2007;Gonzalez et al, 2009;Mune et al, 2009;Lau et al, 2010); (v) fosfatidilserina (PS), fosfatidilcolina (PC), colesterol e (vi) Anexinas, que são uma grande família de proteínas ácidas que se ligam fortemente ao cálcio e PS (Kirsch et al, 1997;Millán, 2006;2013;Golub, 2009;Ciancaglini et al, 2010;Golub, 2011).…”
Section: Biomineralizaçãounclassified